Quality of rubber hospital sheeting - Herminiwati Herminiwati; Arum Yuniari (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1991)
13 (thirteen) samples of Rubber hospital shetting of various trademark which were taken from manufacturers and markets in Bandung, Yogyakarta and Surabaya, had been tested for the purpose of this research. Quality of rubber hospital sheeting is determined by factors that onsure either the strength or wearm by testing them in accorfance with test method as described in ASTM.It could be found from the test results that : the thickness was 0,406 0,506 mm, breaking strength 54,47 – 77,85 kg/cm2. Elongation ata break 99,8% -147,8%.The rubber hospital sheeting was also subjected to hyfrostatic water resistance test and no leakange was accured.It had good steam strikization, accelerated Aging, phenol and alcohol resistance aw well. INTISARI Dalam penelitian ini telah diuji 13 sample perlak karet untuk rumah sakit dari berbagai merk yang diambil langsung dari pabrik maupun pasaran di darah Bandung, DI Yogyakarta dan Surabaya.Mutu perlak karet untuk rumah sakit ditentukan berdasarkan pada factor-faktor yang menajmin menutut ASTM. Dari hasil pengujian diperoleh hasil sebagai berikut tebal 0.406 – 0.506 mm, tegangan putus 54.48 77.85 Kg/cm2, pepanjang putus 99.8 – 147,8 %. Pelak karet yang diuji tidak tembus air dalam pengujian hydrostatic water resistance, juga mempunyai ketahanan terhadap sterilisasi uap, ketahanan terhadap penguasangan, ketahanan terhadap ketahanan terhadap alkokol yang baik.